Co-immobilization and stabilization of xylanase, β-xylosidase and α-l-arabinofuranosidase from Penicillium janczewskii for arabinoxylan hydrolysis - Fanchini Terrasan, César Rafael; Trobo-Maseda, Lara; Moreno-Pérez, Sonia; Carmona, Eleonora Cano [UNESP]; Pessela, Benevides Costa; Guisan, José Manuel (Elsevier, 2016)
Differently activated agarose-based supports were evaluated for co-immobilization of a crude extract from Penicillium janczewskii containing xylanase, β-xylosidase and α-l-arabinofuranosidase activities. Adequately selecting support and immobilization conditions (8 h, using agarose with 10% crosslinking) increased enzyme levels substantially, mainly in relation to the xylanase (2-fold). A coating with dextran aldehyde MW 6000 Da, partially oxidized, covalently attached the enzymes to the support. Optimum activity was verified in the pH range 2-4, and at 50, 65 and 80 °C for the xylanase, α-l-arabinofuranosidase and β-xylosidase, respectively. The xylanase was highly thermostable retaining more than 70% of activity even after 24 h incubation at 60 and 70 °C; and at 80 °C its half-life was 1.7 h. The half-lives of the β-xylosidase and α-l-arabinofuranosidase at 50 °C were 2.3 and 3.8 h, respectively. The co-immobilization of the enzymes on a single support give raise to a functional multi-enzymatic biocatalyst acting in the complete hydrolysis of different and complex substrates such as oat spelt and wheat arabinoxylans, with xylose yield higher than 40%. The xylanase and the α-l-arabinofuranosidase presented high stability retaining 86.6 and 88.0% of activity after 10 reuse cycles.
Keywords: Enzyme co-immobilization; Penicillium janczewskii; Xylan hydrolysis; Xylanase; α-l-arabinofuranosidase; β-xylosidase